Elevated matrix metalloproteinase-2 and -3 production from human diabetic dermal fibroblasts - Wall, S.J.; Sampson, M.J.; Levell, N.; Murphy, G. (British journal of dermatology (1951), 2003)
Summary Background Diabetic foot ulcers are characterized by elevated levels of matrix metalloproteinases (MMP), which could lead to excessive matrix breakdown and disruption to healing. It is unknown if this elevation is a function of wound healing, or if it is present within normal skin and a primary contributor to the increased risk of impaired healing. Objectives To determine whether diabetic fibroblasts from unwounded skin show elevated MMP production compared with their nondiabetic counterparts. Patients and methods Circular skin biopsies (4 mm diameter) were taken from the inside upper arm of four controls without diabetes and from four subjects with insulin‐treated diabetes. Fibroblasts were incubated for a further 72 h and conditioned medium was collected and stored at −20 °C. The conditioned medium was assessed by gelatin zymography and Western blotting for MMP‐2 and MMP‐3. Results Diabetic dermal fibroblasts showed significantly elevated production of MMP‐2 (P < 0·05) and pro‐MMP‐3 (P < 0·05) when compared with their nondiabetic counterparts. Conclusions Dermal fibroblasts from normal unwounded skin are characterized by increased MMP production and this may be a primary contributing factor to the increased risk of nonhealing foot ulceration in diabetes.